1996
DOI: 10.1113/jphysiol.1996.sp021329
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory amino acid‐mediated chemoreflex excitation of respiratory neurones in rostral ventrolateral medulla in rats.

Abstract: 1. In anaesthetized rats, extracellular and intracellular recordings were made from 119 respiratory neurones in the rostroventrolateral reticular nucleus (RVL) of the medulla oblongata. 2. Two types of active respiratory neurones were detected in RVL: expiratory (E) and preinspiratory (Pre-I), based on the relationship between their discharge and that of the phrenic nerve. Some Pre-I but none of the E neurones could be antidromically excited from the C3-C4 level of the spinal cord. 3. E and Pre-I neurones of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 35 publications
0
19
1
Order By: Relevance
“…Examples of Nissl-stained coronal sections of the dorsal CA1 field, revealing densely packed pyramidal cells with well-defined nuclei in control rats (a) and rats subjected to 8 episodes of brief hypoxia (b). Reis, 1994Reis, , 1996 that control cardiovascular and respiratory systems, brain circulation, and other functions are also rapidly and powerfully affected. Hypoxia, depending on intensity and duration, modulates Ca 2ϩ , K ϩ , Na ϩ channel activity and the expression of various genes and induces cellular injury, necrosis, and/or apoptosis (Lopez-Barneo et al, 1988;Sun and Reis, 1994;Hammarström and Gage, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of Nissl-stained coronal sections of the dorsal CA1 field, revealing densely packed pyramidal cells with well-defined nuclei in control rats (a) and rats subjected to 8 episodes of brief hypoxia (b). Reis, 1994Reis, , 1996 that control cardiovascular and respiratory systems, brain circulation, and other functions are also rapidly and powerfully affected. Hypoxia, depending on intensity and duration, modulates Ca 2ϩ , K ϩ , Na ϩ channel activity and the expression of various genes and induces cellular injury, necrosis, and/or apoptosis (Lopez-Barneo et al, 1988;Sun and Reis, 1994;Hammarström and Gage, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Control rats were placed in the same jar for the same period of blowing in air. The intensity of hypoxia was chosen for its sufficiency to produce a brief hypoxic functional interruption, synaptic arrest, of the hippocampal CA1 network, with full recovery immediately after oxygenation in vitro and a brief period of gasping (indicating an activation of respiratory chemoreflex; Sun and Reis, 1996) in vivo, in our preliminary experiments. The neuronal responses to 90% N 2 /5% O 2 /5% CO 2 for 3 min or 95% N 2 /5% CO 2 for 100 s at 31°C were also found to be identical in preliminary experiments.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Data from the present study found that a heterogeneous population of E neurons, including E DEC and E AUG neurons, was excited by exogenous SP. This suggests that endogenous SP and NK1-R may be involved in modulating the excitability of E DEC and E AUG neurons, and these neurons are involved in modulating respiratory rhythm in response to activation of a variety of afferents, including arterial chemoreceptors (Sun and Reis 1996), pulmonary stretch receptors (Hayashi et al 1996), and somatic afferents (Potts et al 2005). It has previously been shown that activation of the slowly adapting pulmonary stretch receptors (SARs) by the HeringBreuer reflex (HB-reflex) excites E DEC neurons in the VRG (Hayashi et al 1996).…”
Section: Reflex Activation Of Nk1-r On Expiratory Neurons Modulates Rmentioning
confidence: 99%
“…These neurons are directly, selectively, rapidly, and reversibly excited in vitro or in vivo by hypoxia Sun and Reis, 1993). Although the elevations in sympathetic, cardiovagal, or respiratory nerve activities are mediated over spinal or intramedullary pathways (Sun and Reis, 1999), hypoxic activation of RVLM neurons elevates rCBF and synchronizes the EEG, and this is not fully understood. Most likely, it is multisynaptic because the RVLM does not innervate the cerebral cortex (Ruggiero et al, 1989).…”
mentioning
confidence: 99%